Analisis konstruksi pipa pompa suction 112-JB - Pungkas Satria; Achmad Widodo; Ismoyo Haryanto; Djoeli Satrijo; Budi Setiyana (Jurnal Material Teknologi Proses: Warta Kemajuan Bidang Material Teknik Teknologi Proses, 2021)
The 101-JTC condenser tank has excess steam condensate due to the addition of admission steam from 101-JT. Therefore, it is necessary to design a piping system that connects 101-JTC condenser tank with the 112-JB pump to drain the condensed excess steam. The designed piping system will encounter a dynamic response caused by fluid flow fluctuation over the time. This dynamic response causes the pipe to experience stress. To find out the resulting voltage which will not cause damage or failure, it is necessary to estimate the safety factor in a piping system that has been given static and dynamic loading. This research uses the fluid structure interaction or FSI method with the help of ANSYS software as a simulation tool. The results of this study are, the flow in the pipe causes an impact load which makes the structure vibrate freely damped. The resulting dynamic response describes, the structure displacement amplitude decreases with increasing time. This indicates a stable vibration. Finally, when viewed from the value of stress against time, the fatigue that occurs in the pipe structure induce a stress below the stress limit on Goodman diagram. It can be estimated that the structure has no service life limit. The fatigue safety factor is 7.1.